A comparison between asymptomatic and symptomatic ureteral stones - Noh, Tae Il; Pyun, Jong Hyun; Shim, Ji Sung; Kang, Seok Ho; Cheon, Jun; Kang, Sung Gu (Scientific reports, 2023)
To investigate the characteristics and impact of asymptomatic (silent) ureteral stones on renal function and compare them with those of symptomatic stones. We retrospectively reviewed the medical records of 677 patients who underwent ureteroscopic lithotripsy or laparoscopic ureterolithotomy for ureteral stones between 2016 and 2020. Patients were divided into two groups according to the presence of recognizable symptoms. We investigated the characteristics and impact of silent stones on post-treatment renal function recovery and compared them with those of symptomatic stones. Among the 677 patients, 43 (6.4%) had asymptomatic ureteral stones, and 634 (93.6%) had symptomatic ureteral stones. Compared to symptomatic stones, asymptomatic stones were larger (11.4 mm vs. 9.6 mm, p = 0.003), more commonly present in the upper ureter (62.7% vs. 48.0%, p = 0.04), and more commonly associated with high-grade hydronephrosis (32.8% vs. 12.3%, p < 0.001); however, no difference in metabolite composition was observed between the two group of stone. In the asymptomatic stone group, the mean preoperative estimated glomerular filtration rate (eGFR) was 77.37 ± 23.54 mL/min/1.73 m 2 , and the mean postoperative eGFR indicated no significant improvement at 1 day, 7 days, 3 months, and 12 months (76.66 ± 21.45, 77.89 ± 20.87, 77.29 ± 22.22, and 76.71 ± 24.21 mL/min/1.73 m 2 , respectively; p = 0.567, p = 0.613, p = 0.924, and p = 0.202, respectively). In the symptomatic stone group, the mean preoperative eGFR was 78.17 ± 28.25 mL/min/1.73 m 2 ; the mean postoperative eGFRs at 1 day, 7 days, 3 months, and 12 months were 81.24 ± 26.38, 86.16 ± 25.61, 89.11 ± 25.43, and 89.50 ± 26.01 mL/min/1.73 m 2 , respectively and demonstrated significant improvement ( p = 0.002, p < 0.001, p < 0.001, and p < 0.001, respectively). Silent stones irreversibly impaired renal function, even after proper management. Therefore, active treatment strategies are required for all patients who are hesitant to receive treatment for silent stones because of their asymptomatic status to prevent permanent renal impairment.